2019
DOI: 10.1039/c8sc02560f
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric maltose neopentyl glycol amphiphiles for a membrane protein study: effect of detergent asymmetricity on protein stability

Abstract: An asymmetric MNG, MNG-8,12, provided enhanced stability to human G protein-coupled receptors (GPCRs) compared to the symmetric MNG, MNG-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
2
22
0
Order By: Relevance
“…Hundreds more detergents have been developed to stabilise MPs further leading to HTP screens to identify the most useful [ 39 , 40 ]. Recently introduced detergents include the neopentyl glycols [ 41 ] and glyco-diosgenin (GDN) which along with digitonin account for around a third of single-particle cryo-EM (cryo-SPA) structures. The recently developed oligoglycerol class is useful for native mass spectrometry [ 42 ].…”
Section: Establishing a Purification Methodsmentioning
confidence: 99%
“…Hundreds more detergents have been developed to stabilise MPs further leading to HTP screens to identify the most useful [ 39 , 40 ]. Recently introduced detergents include the neopentyl glycols [ 41 ] and glyco-diosgenin (GDN) which along with digitonin account for around a third of single-particle cryo-EM (cryo-SPA) structures. The recently developed oligoglycerol class is useful for native mass spectrometry [ 42 ].…”
Section: Establishing a Purification Methodsmentioning
confidence: 99%
“…This analysis assumed that the binding and release cycle of Na + was in the fast-exchange regime. In addition, the CPMG dispersion profile was observed for 23 Na nuclear spins. Although the chemical shifts of Na + bound to A 2A AR and free Na + were similar (Figure 10b), their dispersion profiles indicated that they were not identical and that line broadening caused by intermediate exchange was taking place.…”
Section: ■ Monitoring Interactions Between Gpcrs and Their Environmentmentioning
confidence: 97%
“…However, recently there has been a drive towards developing completely novel detergents that confer, in particular, elevated protein stability, compared with classical detergents. Examples of these include; a new class of steroid-based pentasaccharides [ 6 ], fluorinated glucose and maltose-based detergents [ 7 , 8 ], innovative facial amphiphiles (FAs) [ 9 , 10 ], 1,3,5-triazine-cored detergents [ 11 ], disulfide containing amphiphiles [ 12 ] and modified neopentyl glycol based detergents that have undergone subsequent modification to further improve their characteristics [ 13 ] ( Figure 2 ).…”
Section: Detergentsmentioning
confidence: 99%